Vaccination therapy for inflammatory bowel disease - Yafei Liu; Fei Liao (Human Vaccines & Immunotherapeutics, 2023)
Recently, several novel medications, such as Ustekinumab, Infliximab, and Vedolizumab, have emerged as potential options for inflammatory bowel disease(IBD) management. Despite achieving some effects in clinical applications, these therapies are still plagued by inadequate response rates and adverse side effects. With rapid progress in immunological research, therapeutic vaccines are gaining traction as an alternative. These vaccines aim to activate the body’s immune system to generate specific antibodies, thereby offering a potential avenue for treating IBD. The efficacy and safety of vaccines, coupled with their potential to mitigate the financial and healthcare burden associated with disease treatment, render therapeutic vaccines a more favorable approach for managing patients with IBD. In this review, we critically examine the existing literature pertaining to therapeutic vaccines for IBD, aiming to offer researchers a comprehensive understanding of their applications and prospects and stimulate novel vaccine development by presenting innovative ideas in this field.